Dermal Allograft Patch Augmentation With Mini‐Open Triple‐Row Repair for Large to Massive Rotator Cuff Tears Results in a Low Retear Rate and Favorable Clinical Outcomes Without Adverse Events - Du‐Han Kim; Seong Woo Jeon; Eun‐Seok Son; Chul‐Hyun Cho (Arthroscopy, 2026)
Purpose To evaluate radiological and clinical outcomes, as well as adverse events, after dermal allograft patch (DAP) augmentation with rotator cuff repair for large to massive rotator cuff tears (RCTs). Methods Fifty consecutive patients who underwent DAP augmentation with arthroscopic‐assisted mini‐open triple‐row suture bridge repair for large to massive RCTs were retrospectively reviewed. The inclusion criteria were posterosuperior large to massive RCTs (>3 cm) and a minimum 24‐month follow‐up after surgery. Structural integrity was assessed using either magnetic resonance imaging or ultrasonography at a minimum of 6 months after surgery, and graft incorporation was evaluated using magnetic resonance imaging. Clinical outcomes were sequentially evaluated at baseline and at 3, 6, and 12 months, as well as at the final follow‐up. Results Thirty‐nine patients were included in the final analysis. The mean follow‐up period after surgery was 32.5 (24‐45) months. The overall retear rate was 12.8% (5/39 cases), comprising type 2 retear in 3 cases and type 1 retear in 2 cases. Among the 33 magnetic resonance imaging scans obtained at a mean of 7.1 months after surgery, complete incorporation between the repaired tendon and the patch graft was observed in 8 cases (24.3%), partial incorporation in 17 cases (51.5%), no incorporation in 7 cases (21.2%), and resorption with retear in 1 case (3.0%). No adverse events or complications related to DAP were identified. At final follow‐up, 69.2% of patients achieved the minimal clinically important difference for the visual analog scale pain score, 79.8% for the American Shoulder and Elbow Surgeons score, and 76.9% for the subjective shoulder value. Patient acceptable symptom state was achieved in 72.3%, 75.4%, and 77.5% of patients for the visual analog scale pain score, American Shoulder and Elbow Surgeons score, and subjective shoulder value, respectively. Conclusions DAP augmentation combined with arthroscopic‐assisted mini‐open triple‐row suture bridge repair for posterosuperior large to massive RCTs results in a low retear rate and favorable clinical outcomes without adverse events. Level of Evidence Level IV, retrospective case series.